Walk the walk : the #1 rule for real leaders - Deutschman, Alan, 1965- (New York : Portfolio, 2010)
Arguing that leaders are more effective when they take positive action, a volume of inspiring case stories cites such examples as Martin Luther King, Jr.'s commitment to non-violence, Sony's delay of unproven color television technology, and Southwest Airlines's no-layoffs policy.
Reprint. Originally published: 2009.
Keywords: Leadership